Ultrasound‐guided core biopsy with on‐site cytology‐immediate diagnosis in pediatric oncology. Issue 7 (3rd April 2021) - Sokolovski, Boris; Scolnik, Michal; Malkin, Leonid; Postovsky, Sergey; Weyl Ben‐Arush, Myriam; Ilivitzki, Anat
Abstract: Background: Accurate and swift tissue diagnosis is extremely important for the timely initiation of treatment in pediatric oncology. In our department, ultrasound‐guided core needle biopsy (US‐guided CNB) is used for tissue diagnosis. In 2016, we added on‐site cytology, allowing for an immediate primary diagnosis. We retrospectively reviewed our performance in terms of safety and accuracy for CNBs and on‐site cytology. Methods: All pediatric biopsies performed in our hospital between February 2016 and December 2020, were included. Patient clinical, procedural and follow‐up data were collected. CNB pathology and cytology results were compared to the final pathologic diagnosis. Results: We included 71 patients for which 72 biopsies with on‐site touch imprint (TI) cytology were performed; the average latency time to biopsy was 1 day. Altogether, we had 61 tumors, (58 malignant, 3 benign) and 11 other lesions. On‐site cytology diagnosed 58 malignant tumors, 3 benign tumors and 11 non‐tumor tissues. The cytologist correctly differentiated tumor from inflammation in all cases, and diagnosed the precise tumor type in 57 cases, with an accuracy of 94% for final diagnosis. We had no complications related to the procedure or sedation. Conclusion: US‐guided CNB with on‐site TI cytology for suspected malignancy in the pediatric population is highly available, safe, and accurate, with real‐time diagnosis in most cases. This accelerated diagnostic route has a huge impact on patient care.